2014
DOI: 10.1002/2013gl059130
|View full text |Cite
|
Sign up to set email alerts
|

Electrodynamics of the Martian dynamo region near magnetic cusps and loops

Abstract: Strong and inhomogeneous remanent magnetization on Mars results in a complex pattern of crustal magnetic fields. The geometry and topology of these fields lead to atmospheric electrodynamic structures that are unique among the bodies of the solar system. In the atmospheric dynamo region (∼100−250 km altitude), ions depart from the gyropath due to collisions with neutral particles, while electron motion remains governed by electromagnetic drift. This differential motion of the charge carriers generates electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…The fact that the peak electron densities are somewhat larger in areas with vertical crustal magnetic fields seems to be consistent with this picture [ Gurnett et al , ; Duru et al , ; Nielsen et al , ]. Moreover, localized electrodynamic effects due to ionospheric dynamo processes take place in areas of strong crustal magnetic fields and alter the ionospheric behavior [ Withers et al , ; Riousset et al , ]. However, the effect of the crustal magnetic fields on the electron densities at altitudes close to the peak altitude is overall small compared to typical N11 model inaccuracies, i.e., including the crustal magnetic field effects would not significantly alter the model performance close to the peak altitude.…”
Section: Discussionmentioning
confidence: 90%
“…The fact that the peak electron densities are somewhat larger in areas with vertical crustal magnetic fields seems to be consistent with this picture [ Gurnett et al , ; Duru et al , ; Nielsen et al , ]. Moreover, localized electrodynamic effects due to ionospheric dynamo processes take place in areas of strong crustal magnetic fields and alter the ionospheric behavior [ Withers et al , ; Riousset et al , ]. However, the effect of the crustal magnetic fields on the electron densities at altitudes close to the peak altitude is overall small compared to typical N11 model inaccuracies, i.e., including the crustal magnetic field effects would not significantly alter the model performance close to the peak altitude.…”
Section: Discussionmentioning
confidence: 90%
“…It is interesting to point out that both hybrid models [e.g., Brecht and Ledvina, 2014a] and other MF-MHD codes [e.g., Harnett and Winglee, 2006] also showed that the crustal field has a strong shielding effect to protect Mars from the solar wind interaction regardless of different model setups and inputs. Meanwhile, Riousset et al [2014] pointed out that the ionospheric outflows are likely to be prevented when the surface and lower atmospheres are shielded by closed field lines due to the presence of magnetic loops and arcades. Such shielding ultimately reduces the fluxes of ions from the dynamo region to the upper ionosphere and thus reducing the ion escape rate.…”
Section: Effects Of Crustal Field Orientationmentioning
confidence: 99%
“…Thus, the use of global simulations is necessary. Various plasma models based on different assumptions, i.e., test particle model [Fang et al, 2010;Curry et al, 2013Curry et al, , 2014Curry et al, , 2015, multispecies MHD model [Ma et al, 2004;Ma and Nagy, 2007;Ma et al, 2014], multifluid MHD model [Harnett and Winglee, 2006;Najib et al, 2011;Riousset et al, 2013Riousset et al, , 2014Dong et al, 2014], and kinetic hybrid model [Modolo et al, 2012;Brecht and Ledvina, 2014a] have been used to simulate the solar wind interaction with the Martian upper atmosphere and calculate the associated ion escape rates. An ongoing International Space Studies Institute effort focused upon the global models and measurements of the Martian plasma environment being led by Professor David Brain at the University of Colorado, Boulder, CO [Brain et al, 2010[Brain et al, , 2012, allows intercomparison of these multidimensional plasma codes, which will benefit the entire community.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure , a selected region of strong crustal field is compared with the field produced by a simplified dipole. In Figure a we show arcade‐like looped field lines of a strong crustal field region at Mars [e.g., Riousset et al ., ], located between 50°S and 68°S, centered at 180°E and spanning ~18° in latitude. The simplified dipole analog shown in Figure b has a field strength of ~1000 nT at the lower boundary and ~100 nT at the upper boundary and has a similar spatial extent to the observationally constrained field in Figure a.…”
Section: Model Descriptionmentioning
confidence: 99%